10th North American Caribou Workshop, 4-6 May 2004, Girdwood, Alaska, USA. - Haugerud (ed. in chief), Rolf Egil; McCarthy, Laura; Valkenburg (issue eds.), Patrick (Rangifer, 2005)
180 people attended the 10th North American Caribou Workshop at Girdwood near to Anchorage.